A (New) Country Insurance Facility - Cordella, Tito (IMF Working Papers; Working Paper, 2005)
To cope with the self-fulfilling liquidity runs that triggered many recent financial crises, we propose the creation of a country insurance facility. The facility, which we envisage as complementary to the existing multilateral lending facilities, would provide eligible countries with automatic access to a credit line at a predetermined interest rate. Eligibility criteria should be easily verifiable, focus on debt sustainability, and take into account the currency and maturity composition of the debt. Other critical design issues considered here include the size of the facility, its duration and charges, and the exit costs for a country that loses eligibility.